Mind the Gap: Bridging the Perception and Reality of Crime Rates with Information - Martin Ardanaz; Ana Corbacho; Mauricio Ruiz-Vega (Inter-American Development Bank (IDB), 2014)
Gains from government crime-reducing programs are not always visible to the average citizen. The media overexpose crime events, but the absence of crime rarely makes the news, increasing the risk that citizen may have inaccurate perceptions of security. Through a survey experiment carried out in Bogota, Colombia, a city that experienced a substantial reduction in homicides over the last decade, as well as a noticeable drop in robberies, this paper tests the effect that communicating objective crime trends could have on such perceptions. The results show that information improves perceptions of safety and police effectiveness, and lowers distrust in the police. However, the information treatment is not able to impact those with biased priors, and tends to weaken over time. A more active and regular engagement with citizens regarding these trends is needed to bridge the gap between perception and reality.
hdl:11319/6595
Keywords: I38; R28; 330; Information; Beliefs; Perception; Crime